Evaluation of European-based polygenic risk score for breast cancer in Ashkenazi Jewish women in Israel - Levi, Hagai; Carmi, Shai; Rosset, Saharon; Yerushalmi, Rinat; Zick, Aviad; Yablonski-Peretz, Tamar; Wang, Qin; Bolla, Manjeet K.; Dennis, Joe; Michailidou, Kyriaki; Lush, Michael; Ahearn, Thomas; et al. (Journal of Medical Genetics, 2023)
To date, most BC GWASs have been performed Background Polygenic risk score (PRS), calculated in individuals of European (EUR) ancestry, and based on genome-wide association studies (GWASs), the generalisation of EUR-based PRS to other can improve breast cancer (BC) risk assessment. populations is a major challenge. In this study, we examined the performance of EUR-based BC PRS models in Ashkenazi Jewish (AJ) women. Methods We generated PRSs based on data on EUR women from the Breast Cancer Association Consortium (BCAC). We tested the performance of the PRSs in a cohort of 2161 AJ women from Israel (1437 cases and 724 controls) from BCAC (BCAC cohort from Israel (BCAC-IL)). In addition, we tested the performance of these EUR-based BC PRSs, as well as the established 313-SNP EUR BC PRS, in an independent cohort of 181 AJ women from Hadassah Medical Center (HMC) in Israel. Results In the BCAC-IL cohort, the highest OR per 1 SD was 1.56 (±0.09). The OR for AJ women at the top 10% of the PRS distribution compared with the middle quintile was 2.10 (±0.24). In the HMC cohort, the OR per 1 SD of the EUR-based PRS that performed best in the BCAC-IL cohort was 1.58±0.27. The OR per 1 SD of the commonly used 313-SNP BC PRS was 1.64 (±0.28). Conclusions Extant EUR GWAS data can be used for generating PRSs that identify AJ women with markedly elevated risk of BC and therefore hold promise for improving BC risk assessment in AJ women.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Genomics; Polymorphism; Genetic